ENHANCING FINANCIAL ACCOUNTABILITY OF ISLAMIC PHILANTHROPIC ORGANIZATIONS THROUGH FINANCIAL DISCLOSURE - Hisham Kamaruddin, Muhammad Iqbal; Ramli, Nathasa Mazna (Online Journal of Research in Islamic Studies, 2015)
Philanthropic organizations or known as non-profit organizations in Malaysia currently having a high growth from it first existence from decades ago. The growth creates, among others, an issue on accountability especially on financial accountability. The aim of this article is to discuss the concept of accountability related to Islamic philanthropic organizations. This article also highlights financial disclosure as one of the mechanism to ensure financial accountability in these institutions. Discussion of this paper opens to potential development of specific financial disclosure for Islamic philanthropic organizations, which could become one of the tools for trustee to discharge its accountability